Tauhid dalam Studi Tasawuf - Ilyas Arya (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss monotheism in the study of tasawuf. This study uses a qualitative approach by applying a descriptive-analytical method. The results and discussion in this study show that monotheism in the perspective of tasawuf. Tauhid for Sufis is not only verbal recognition, but has been transformed and institutionalized in such a way from the experience of Sufis that it becomes an understanding of unity between humans and God (ittihad) which in this case is the union between the human spirit and God. This study concludes that Sufism has its own perspective with other sciences, Sufism will further in depth view the notion of monotheism not only verbal recognition and utterance but has a deeper meaning than that.